Abuse of Power: Tinjauan Terhadap Penyalahgunaan Kekuasaan oleh Pejabat Publik di Indonesia - Raden Imam Al Hafis; Moris Adidi Yogia (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
Having power means having the ability to change the behavior or attitudes of others in accordance with what is desired by the authority. By holding power, automatically the bersangkuatan has an influence, and this is what is dreamed by some people who want to get legitimacy so that later he has the influence of the power possessed. the cause of abuse of power can have an impact on rampant corruption. Among the causes: a. That punishment perceived from the results of abuse of power is relatively lighter compared to the benefits it feels. b. Abuse of power can be tricked and engineered in the form of physical accountability. c. To get power requires substantial material capital, so that when the power is granted to him, of course the person concerned is trying to return the initial capital plus a large profit. d. It is not good for a check and balance system in the government system.